Successful pregnancy after preimplantation genetic testing for structural rearrangements in a couple with complex chromosome rearrangement and recurrent in vitro fertilization failures: a case report - Divyesh Upadhyay, B.S.; Rajia Al Halaby, M.D.; Sudha Anandt, Ph.D.; Firas Albuz, Ph.D.; Merlin Mary Varghese, M.S.; Braulio Peramo, M.D. (F&S Reports)
Objective: To present a case of a couple with 20 years of infertility and 10 recurrent in vitro fertilization (IVF) failures, identifying a paternal complex chromosome rearrangement using high-resolution karyotype together with preimplantation genetic testing for structural rearrangements (PGT-SR) and utilizing IVF-intracytoplasmic sperm injection to achieve a successful pregnancy. Design: Case report. Setting: Al Ain Fertility Center, Abu Dhabi, United Arab Emirates. Patients: A 40-year-old male patient and a 37-year-old female patient with a history of infertility and recurrent IVF failures. Exposure: In vitro fertilization-intracytoplasmic sperm injection with high-resolution karyotype and PGT-SR. Main Outcome Measures: Identification of chromosomal abnormalities, successful embryo development, pregnancy outcome, and newborn karyotyping. Results: Karyotyping revealed a paternal complex chromosome rearrangement, t(3;4;12) (q21;q33;q21), and a chromosomal polymorphism in the female (1qh+). In vitro fertilization-intracytoplasmic sperm injection with PGT-SR produced one euploid/balanced female embryo from 20 embryos across 8 cycles. The patient conceived after hormone replacement therapy and frozen embryo transfer, resulting in an uneventful, full-term pregnancy and delivery of a healthy baby via C-section. Newborn karyotyping was normal (46,XX). Conclusion: High-resolution karyotype and PGT-SR should be offered to patients undergoing IVF, especially those with severe male factors, recurrent IVF failures, implantation failures, or recurrent pregnancy losses, to enhance the chances of a successful pregnancy.